TINJAUAN YURIDIS STATUS TANAH DALAM PEMBAHARUAN HAK GUNA BANGUNAN: Jurdicial Review Of Land Status In Building Use Right Renewal - Fadhila Rizqia Fananny; Irene Eka Sihombing (Faculty of Law, Universitas Trisakti, 2025)
Land disputes are still one of the main problems in Indonesia that often arise, one of which concerns Building Rights Title, which is a form of land rights regulated in Article 35 of Law Number 5 of 1960 concerning Basic Agrarian Principles. This research discusses legal issues related to the renewal of PT Indobuildco's Building Rights Title (HGB) on Sultan Hotel land, which was rejected by the government even though the applicant had fulfilled administrative requirements. The research analyze the legal status of the disputed land and the implications of the rejection of the HGB renewal on legal certainty. The method used is normative juridical with secondary data analysis in form of laws and regulations, legal theories, and supporting documents. The results show that the refusal to renew the HGB has an impact on the uncertainty of land status, which hinders the implementation of legal obligations by private subjects. This refusal decision must fulfill the good governance principles, such as transparency and accountability. The conclusion of this research is that the case of PT Indobuildco's HGB renewal on Sultan Hotel land reflects the lack of legal certainty in the management of state land, especially related to HGB and HPL disputes.